A juventude e o consumo de drogas nas séries Skins e Euphoria - Santos, Joyce Felix dos (2025)
The use of psychoactive substances among young people is a multifaceted phenomenon, shaped by subjective, social, and cultural dimensions that go beyond epidemiological statistics. The media, as a producer of meaning, plays a fundamental role in shaping symbolic understandings of these practices, especially when drug use is repeatedly depicted in widely consumed cultural products. This dissertation investigates how drug consumption is represented in the television series Skins and Euphoria, through a content analysis of 77 episodes. The aim is to identify narrative patterns, recurring motivations, types of substances depicted, and the consequences associated with drug use in both shows, exploring how these elements contribute to the symbolic construction of the youth drug user. The analysis revealed a predominance of scenes portraying routine drug use and consumption as a coping mechanism for emotional pain—often depicted in normalized contexts with little explicit critical reflection. The consequences shown typically revolve around cycles of self-destruction and psychological distress, with rare representations of recovery or resolution. While the absence of moralizing discourse allows for more complex portrayals, it also risks banalizing high-risk behaviors. In light of communication and behavioral theories—such as Social Learning Theory, Cultivation Effects, and the Normalization Theory—this study emphasizes the importance of understanding media’s role in mediating values and behaviors, particularly in contexts of youth vulnerability. Rather than merely reflecting reality, audiovisual narratives help to shape it symbolically. Therefore, this research underscores the relevance of critical and interdisciplinary analyses of drug use portrayals in media, especially as they relate to contemporary youth experiences of belonging, emotional pain, and identity formation.